Réponses

2014-05-05T21:27:11+02:00
y = -2/3x + 5/3
y = 5/4x + 1


y = 5/4x + 1
-5/4x = 1 - y
x = -4/5 + 4/5y

On a :
y = -2/3 (-4/5 + 4/5y) + 5/3
y = +8/15 - 8/15y + 5 x 5 / 3 x 5
y = 8/15 - 8/15y + 25/15
y = - 8/15y + 25/15 + 8/15
y = - 8/15y + 33/15
y + 8/15y = 33/15
15/15y + 8/15y = 33/15
23/15y = 33/15
y = 33/15  x 15/23
y = 33/23

x = -4/5 + 4/5y
x = - 4/5 + 4/5 (33/23)
x = - 4/5 + 132/115
x = -4 x 23 / 5 x 23 + 132/15
x = - 92/115 + 132/15
x = 40/115
x = 5 x 8 / 5 x 23
x = 8/23


Les solutions sont : (8/23 ; 33/23)